ANALYSIS OF LNG CARRIER PROPULSION DEVELOPMENTS - Domić, Ivica; Stanivuk, Tatjana; Stazić, Ladislav; Pavlović, Igor (Journal of Applied Engineering Science, 2022)
The LNG market has undergone major changes and significant development in recent years. With the increase in the number of ships and the increase in the amount of gas transported, the propulsion machinery of LNG ships has also changed. For many years, the steam turbine was the only propulsion engine on this type of cargo ship. A negligible number of vessels powered by a traditional, low-speed, heavy-duty diesel engines are increasingly being replaced by new technologies. Versions of dual-fuel internal combustion engines that burn evaporated natural gas are increasingly replacing steam turbine propulsion systems. This phenomenon has been particularly pronounced in the last few years, when orders for steam turbine-powered LNG vessels have ceased. This article examines and presents the main reasons for these changes, which fall into two categories. The first is financial, as the use of new technologies can lead to significant financial savings in fuel consumption. Fuel costs can be reduced by more than 35% in some cases. The reduction in fuel consumption leads to a significant reduction in overall exhaust emissions and thus a reduction in air pollution and CO2 signature.
Keywords: LNG fleet, LNG ships, ship propulsion, air emission, fuel consumption